The source of water and High prevalence of Helicobacter pylori Infection in Asymptomatic Children and Adults. How is Important. (Journal of Humanitarian and Applied Sciences, 2020)
Helicobacter pylori infections occur earlier in life with high frequency in developing countries. It has been reported that the source of drinking water as a potential route of transmission. There is no information available regarding the prevalence of H. pylori infection in asymptomatic children and adults, and its associated risk factors in rural 209regions. Objectives: To establish the current prevalence of H. pylori infection among asymptomatic Secondary- School and university students in Kasr Khiar city and its associated risk factors. Materials and Methods: A Blood sample of (125) healthy students of two secondary schools, and (100) healthy adult students of Faculty of Arts & Sciences, Al- Merghib University in Kasr Khiar city, using immunochromatographic rapid method to detect anti-H. pylori IgG, and questionnaire covering Sociodemographic variables were completed by interview. Results: overall, seroprevalence of H. pylori was 85% in the healthy university students, there was a gradual increase with age, and no statistical difference between genders. However, H. pylori was 65%, 81% in the secondary school bR\V¶ childUeQ, VecRQdaU\ VchRRl giUlV¶ childUeQ UeVSecWiYel\. The higheVW SeUceQWage Rf positive infected H. pylori in subjects who are using private untreated well-water drinking than those the commercial water supply. Conclusions: The prevalence of H. pyloriinfection is high among the secondary school healthy students, as well as the university adult students in Kasr Khiar region, which might be related to the socioeconomic status, and living conditions, as major risk factors for H. pylori infection. Our data indicate that the source of drinking water is an important mechanism for the transmission of H. pylori in a rural region. However, larger studies in other regions of Libya should be conducted to confirm the study finding, using molecular typing techniques to help trace the route of transmission in future
Keywords: Helicobacter pylori; Prevalence; Serology; Asymptomatic; Libya